Hierarchical microstructure of CNTs interwoven ultrathin Co3S4 nanosheets as a high performance anode for sodium-ion battery. Issue 3 (15th February 2019) - Liu, Dongning; Hu, Aiping; Zhu, Yanfei; Zhou, Shengping; Duan, Yu; Tang, Qunli; Deng, Weina; Chen, Xiaohua
Abstract: In this work, Co3 S4 /CNTs three-dimensional hierarchical microstructure has been synthesized through a facile sulfidation method with Co3 O4 /CNTs as precursor. Particularly, by controlling hydrothermal time, the optimized Co3 S4 /CNTs-9 composite consists of ultrathin and rich mesoporous Co3 S4 nanosheets (< 10 nm) with CNTs firmly intertwined inside microstructures. Benefitting from the porous and robust secondary-structure, as well as the intertwined CNTs among ultrathin active materials Co3 S4 nanosheets, Co3 S4 /CNTs-9 electrode provides fast efficient ways of ion and electron transportation. As a result, it exhibits an excellent rate performance. Charge capacity retention at 1 A g −1 is up to 80% compared with 0.1 A g −1 . The enhanced extrinsic pseudocapacitive contribution is confirmed at higher rate through the cyclic voltammetry analysis at different scan rates of Co3 S4 /CNTs-9 electrode. Importantly, Co3 S4 electrode also exhibits a high initial coulombic efficiency of 82.89%, which suggests that Co3 S4 is a promising anode candidate for sodium-ion batteries.